Evaluation of serum chondroitin sulfate and hyaluronan: Biomarkers for osteoarthritis in canine hip dysplasia - Nganvongpanit K. (2014)
Hip dysplasia (HD) is one of the most important bone and joint diseases in dogs. Making the radiographic diagnosis is sometime possible when the disease has markedly progressed. Chondroitin sulfate (CS) and hyaluronan (HA) are the most important cartilage biomolecules that are elevated in the serum taken from dogs with osteoarthritis. The serum CS and HA can be detected by an ELISA technique, with using monoclonal antibodies against CS epitope 3B3 and WF6 and the HA chain as the primary antibodies. The aim of this study was to compare the levels of serum CS (both epitopes) and HA in non-HD and HD dogs. All 123 dogs were categorized into 2 groups. The non-HD group was composed of 98 healthy dogs, while the HD group was comprised of 25 HD dogs. Blood samples were collected for analyzing the serum CS and HA levels with using the ELISA technique. The results showed that the average serum level of the CS epitope WF6 in the HD group (2,594 ± 3,036.10 ng/ml) was significantly higher than that in the non-HD group (465 ± 208.97 ng/ml) (p < 0.01) while the epitope 3B3 in the HD group (105 ± 100.05 ng/ml) was significantly lower than that in the non-HD group (136 ± 142.03 ng/ml) (p < 0.05). The amount of serum HA in the HD group (134.74 ± 59.71 ng/ml) was lower than that in the non HD group (245.45 ± 97.84 ng/ml) (p < 0.05). The results indicate that the serum CS and HA levels might be used as biomarkers for osteoarthritis in HD dogs.